2022
DOI: 10.3390/pr10020406
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Control in Decontamination of Sludge from Wastewater Treatment Plant

Abstract: Dynamics of the microbiological indicators of fresh sludge from wastewater treatment plants with a concentration of CaO, 10% and 20%, and ash, −30% and 50%, and treated with quicklime, ash, and microbial fertilizer for a 50-day period of composting were studied. The influence of temperature, water content, and oxygen on the development of microbes was established in laboratory conditions. Microbiological analysis included the determination of non-pathogenic (non-spore-forming bacteria, bacilli, actinomycetes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…We are aware that quicklime needs wise management decisions before using either in the terrestrial or aquatic environment, since in water at high concentrations can be dangerous to mollusks and fish [ 44 ]. Compared to the CaO concentrations used to treat sludge from wastewater treatment plants (up to 20%, w / v ) [ 14 ], the amounts used in this study are much lower. Nevertheless, precautions are needed before applying it specifically as a disinfectant, and more studies are needed on its potential application in beach sand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are aware that quicklime needs wise management decisions before using either in the terrestrial or aquatic environment, since in water at high concentrations can be dangerous to mollusks and fish [ 44 ]. Compared to the CaO concentrations used to treat sludge from wastewater treatment plants (up to 20%, w / v ) [ 14 ], the amounts used in this study are much lower. Nevertheless, precautions are needed before applying it specifically as a disinfectant, and more studies are needed on its potential application in beach sand.…”
Section: Discussionmentioning
confidence: 99%
“…Reported remediation measures include sand removal and treatment by chlorine, to restore the biosafety sand quality [ 1 ]. Besides, quicklime used at 10–20% concentration ( w / v ) was reported as an effective treatment for highly contaminated sludges from wastewater plants [ 14 ]. Based on these observations, we tested the potential use of quicklime as a possible rapid sand decontamination method, by using low concentrations of quicklime (1–3%, w / w ) mixed with sand, and analyzing over time its impact on the whole beach sand microbial population, as well on the fraction of potential human pathogens and on the environmental microbes.…”
Section: Introductionmentioning
confidence: 99%
“…However, this could be beneficial since the results presented by Malcheva et al showed that the creation of an alkaline environment led to a reduction in the number of beneficial microorganisms. This can be used to reduce or destroy pathogenic microorganisms in sewage sludge, compost, and organic waste [27].…”
Section: Discussionmentioning
confidence: 99%
“…Sustainability 2022, 14, x FOR PEER REVIEW 8 of 11 reduce or destroy pathogenic microorganisms in sewage sludge, compost, and organic waste [27]. Considering the large group of Proteobacteria in the analyzed samples, it should be noted that two classes of microorganisms dominated: Alphaproteobacteria and Gammaproteobacteria, for which 18 and 16 representatives were identified, respectively (Figure 4).…”
Section: Community Of Bacteria Structure Changesmentioning
confidence: 99%
“…In addition, the use of microalgae in effluent sanitation is crucial to reducing or eliminating pathogens through mechanisms such as pH changes, nutrient competition, fixation, sedimentation, presence of biocontrol agents (Dar et al, 2019). During photosynthesis, an increase in pH and oxygen concentration occurs, which affects the growth of pathogens such as total and fecal coliforms, Salmonella, Clostridium, and Enterococcus (Delanka- Pedige et al, 2019;Cho et al, 2022;Malcheva et al, 2022). Many produced microalgae metabolites have an antimicrobial effect, being more marked in gram-positive bacteria than in gram-negative bacteria, a difference that is linked to the changes evidenced in the type of cell wall structure (Ramírez- Mérida et al, 2015a;Polat et al, 2023).…”
Section: Role Of Microalgae In the Biological Treatment Of Wastewatermentioning
confidence: 99%